Involvement of Met receptor pathway in aggressive behavior of colorectal cancer cells induced by parathyroid hormone-related peptide - Novoa Díaz, María Belén (2022)
Parathyroid hormone-related peptide (PTHrP) plays a key role in the devel opment and progression of many tumors. We found that in colorectal cancer (CRC) HCT116 cells, the binding of PTHrP to its receptor PTHR type 1 (PTHR1) activates events associated with an aggressive phenotype. In HCT116 cell xenografts, PTHrP modulates the expression of molecular markers linked to tumor progression. Empirical evidence suggests that the Met receptor is involved in the development and evolution of CRC. Based on these data, we hypothesized that the signaling pathway trigged by PTHrP could be involved in the tran sactivation of Met and consequently in the aggressive behavior.